Exploring the mediating role of social support and learning engagement in the relationship between physical activity and academic achievement in secondary school students - Xiang, Jun; Guo, Kelei; Gao, Jia; Gao, Yun; Liu, ShiLei (Frontiers in Psychology, 2025)
BackgroundThe academic achievement of secondary school students has consistently been a focal topic of interest among researchers. However, the relationship between physical activity and academic achievement, along with its underlying mechanisms, remains unclear. Therefore, the purpose of this study was to investigate the relationship between physical activity and academic achievement of secondary school students, and to verify the mediating role of social support and learning engagement between them.MethodsBased on the purpose, a survey was conducted involving 3,230 secondary school students (M age = 13.21, SD age = 0.54) in Guangdong Province, utilizing the Physical Activity Level Scale, Academic Achievement Scale, Perceived Social Support Scale, and Learning Engagement Scale. Data were statistically analysed using descriptive statistics, correlation analysis, regression analysis and mediation analysis by using SPSS to examine the relationship between physical activity and academic achievement, as well as the mediating roles of social support and learning engagement.ResultsIndependent Sample t-test were used to test gender differences, which were observed only in physical activity, with boys exhibiting significantly higher scores than girls (Boys: 36.41 ± 19.17; Girls: 34.21 ± 19.78; p = 0.008). ANOVA were used to test age differences, which were observed in physical activity (F = 3.426, p = 0.001) and learning engagement (F = 3.054, p = 0.012), with physical activity declining among middle school students as age increased, while learning engagement showed a continuous rise across all age stages. Regression analysis showed that the direct path from physical activity to academic achievement was significant (β = −0.025, p < 0.01). Physical activity positively predicted social support (β = 0.085, p < 0.01) and learning engagement (β = 0.082, p < 0.01). Social support significantly predicted learning engagement (β = 0.096, p < 0.01) and academic achievement (β = −0.038, p < 0.01). Social support and learning engagement play significant mediating roles in the relationship between physical activity and academic achievement, accounting for 90.25% of the total effect. The mediating effect consists of three pathways: (1) physical activity → social support → academic achievement (mediating effect is 0.017), (2) physical activity → learning engagement → academic achievement (mediating effect is 0.032), and (3) physical activity → social support → learning engagement → academic achievement (mediating effect is 0.062).ConclusionPhysical activity not only directly predicts academic achievement in middle school students, but also directly through the separate mediating roles of social support and learning engagement, and indirectly through the chained mediating roles of social support and learning engagement. These findings underscore the significant influence of physical activity on academic achievement, offering valuable insights for educators in developing and implementing strategies that foster students’ academic development.